A GSH Fluorescent Probe with a Large Stokes Shift and Its Application in Living Cells - Mao, Yueyuan (Sensors (Basel), 2019)
Intracellular GSH is the most abundant non-protein biothiol and acts as a central antioxidant to defend against aging toxins and radicals. Meanwhile abnormal level of intracellular GSH concentration is directly related to some diseases. In this case, detecting intracellular GSH rapidly and sensitively is of great significance. We synthesize a simple fluorescent probe (named GP) which can discriminate GSH from Cys (cysteine) or Hcy (homocysteine) and presents a 50-fold fluorescence increasing. The response time of GP to GSH was only 5 min and the product GO (the product of GP after reacting with GSH) after reacting with GSH possesses a larger Stokes shift for 135 nm than that in reported work. Probe GP can detect intracellular effectively and shows obvious yellow fluorescence. Briefly, probe GP can detect intracellular GSH rapidly and effectively both in vitro and in living cells.